The determinants of international equity investment: Do they differ between institutional and noninstitutional investors? - Roque, Vanda (2016)
In this paper we investigate whether the determinants of international equity investment differ between investors with different degrees of sophistication. For this purpose, we analyse and compare the determinants of international equity investment of institutional and noninstitutional investors from 20 OECD countries (US not included) in the period 2001-2009. The results show that there are significant differences in the determinants of international equity investment between institutional and noninstitutional investors. In particular, noninstitutional investors tend to exhibit a more pronounced preference for equities of geographical nearby, contiguous and more transparent countries than institutional investors. The preference for more developed equity markets and the contrarian behaviour are also significantly more pronounced for noninstitutional than for institutional investors. These results support the argument that international equity investment of less sophisticated investors is more affected by information costs and familiarity than that of more sophisticated investors. Moreover, business cycles exert an influence on international equity investment decisions of both institutional and noninstitutional investors.